(untitled) (Third Sector Social Economic Review, 2010)
Poverty is the case where the income obtained cannot encounter the minimum needs required to survive. The limitations caused by economical crises, natural disasters, migrations, wars, globalization and structural orientation programs experienced all over the world and also in our country both increase the level of poverty and create new poor. Poverty obviously affects the whole family. However, the roles put on woman for the responsibilities concerning the wealth of family make the duty of woman much harder. Woman poverty is a multidimensional problem. In a society, the structural inequality between woman and man and women make their ways of experiencing poverty and relative poverty different. One of the major reasons of woman poverty is that woman is deprived of an income. The rates of participation of woman into labor force in our country have never been so high. The efforts of strengthening comprise one of the legs of the struggle with woman poverty. Strengthening will also lead to the fact that woman is aware of what she does, think of her life and interfere with it.